Understanding the Method Effects of the Ethnic Identity Scale Items - Qothrun Nada; Sukaesi Marianti (Jurnal Psikologi, 2021)
This study used the Correlated Traits-Correlated Method (CTCM) model to identify the method effects of the Ethnic Identity Scale (EIS) items, both in favorable and unfavorable items. The study involved 4 alternative models of the CTCM to test the suitability of the model. 440 secondary-school students were involved in this study. Confirmatory Factor Analysis was used employing R software Version 4.0.2. Results indicated alignments between the data with three CTCM alternative models that provided evidence to understand the effect of the method on the use of positive and negative items that could affect the validity of a measuring instrument.